Sand flies of the endemic areas of American cutaneous leishmaniasis in Paraty, Rio de Janeiro, Brazil - MOUTINHO, FLÁVIO FERNANDO B.; BARBOSA DE SOUZA, MARCOS; DE CARVALHO, RAIMUNDO WILSON (Revista Colombiana de Entomología, 2010)
The municipality of Paraty has a high incidence of American Cutaneous Leishmaniasis (ACL), with an annual mean of 43.2 cases since 1985. The municipality is of great importance for tourism activities given its historic importance and landscape characteristics. It receives thousands of international and national tourists annually. Studies on the sand fly fauna were carried out in seven localities with reports of human or canine cases of ACL, in order to provide new information to help prevent ACL. A total of 3,831 specimens were collected belonging to seven species: Nyssomyia intermedia, Migonemyia migonei, Micropygomyia schreiberi, Pintomyia fischeri, Evandromyia tupynambai, Lutzomyia longipalpis, and Exapillata firmatoi. The species N. intermedia was predominant, followed by M. migonei and L. longipalpis. The major peak of sand fly densities in Ponta da Romanã occurred between the ranges of 18 to 19 h and 01 to 02 h. En the locality of Pouso da Cajaíba, the peaks occurred between 19 to 20 h and 01 to 02 h. We suggest that the species N. intermedia and M. migonei are transmitting American cutaneous leishmaniasis in the endemic areas of Paraty, Rio de Janeiro, Brazil.